The Development and Implementation of M-Edupayment: A Multi-Payment Platform for SMK Negeri 7 Bandar Lampung - Praseptiawan, Mugi; Utoro, Meida Cahyo; Ashari, Ilham Firman; Algifari, Muhammad Habib; Afriansyah, Aidil (Jurnal Pengabdian kepada Masyarakat (Indonesian Journal of Community Engagement), 2025)
This community engagement activity aimed to develop a mini bank website, m-EduPayment, integrated with the iPaymu payment gateway as an Application Programming Interface (API). The project was implemented at SMK Negeri 7 Bandar Lampung. System development followed the Personal Extreme Programming (PXP) method, which included the stages of Requirements, Planning, Iteration Initialization, Design, Implementation, and System Testing. PXP, a variant of Extreme Programming, was specifically adapted for individual developers. The activity involved 31 respondents, consisting of 10th and 11th-grade students, who evaluated the system using the System Usability Scale (SUS) to measure its usability. Interviews with teachers (superadmins) and student administrators were also conducted to identify initial requirements and gather feedback on the system design. Data analysis utilized a Likert scale, where respondents rated various system aspects on a scale from 1 (strongly disagree) to 5 (strongly agree). SUS scores were calculated using standard formulas to determine a final score, which was then classified into usability categories. The average SUS score was 91, falling under the "Excellent" category (Grade A). The development of the mini bank website introduced new features, including online payment services for tuition fees (SPP), waste banks, and savings. System testing achieved a 99% functional success rate, demonstrating the platform’s high usability in the school environment. Respondents provided overwhelmingly positive feedback, affirming the successful implementation and functionality of the website.